Blue sclera syndrome - Loja, David (2002)
We present a case of a 35 year-old woman who had multiple bony fractures, short size, left xyphoescoliosis, blue sclerae, functional limitation of the hips, dentinogenesis imperfecta, severe osteoporosis and conduction hypoacusia. We review the types of osteogenesis imperfecta, clinical presentation, differential diagnosis, treatment and prognosis.